How quantum brain biology can rescue conscious free will - Hameroff, Stuart (Frontiers in Integrative Neuroscience, 2012)
Conscious ‘free will’ is problematic because 1) brain mechanisms causing consciousness are unknown, 2) measurable brain activity correlating with conscious perception apparently occurs too late for real-time conscious response, consciousness thus being considered ‘epiphenomenal illusion’, and 3) determinism, i.e. our actions and the world around us seem algorithmic and inevitable. The Penrose-Hameroff theory of ‘orchestrated objective reduction’ (‘Orch OR’) identifies discrete conscious moments with quantum computations in microtubules inside brain neurons, e.g. 40 per second in concert with gamma synchrony EEG. Microtubules organize neuronal interiors and regulate synapses. In Orch OR, microtubule quantum computations occur in integration phases in dendrites and cell bodies of integrate-and-fire brain neurons connected and synchronized by gap junctions, allowing entanglement of microtubules among many neurons. Quantum computations in entangled microtubules terminate by Penrose ‘objective reduction’ (‘OR’), a proposal for quantum state reduction and conscious moments linked to fundamental spacetime geometry. Each OR reduction selects microtubule states which can trigger axonal firings, and control behavior. The quantum computations are ‘orchestrated’ by synaptic inputs and memory (thus ‘Orch OR’). If correct, Orch OR can account for conscious causal agency, resolving problem 1. Regarding problem 2, Orch OR can cause temporal non-locality, sending quantum information backward in classical time, enabling conscious control of behavior. Three lines of evidence for brain backward time effects are presented. Regarding problem 3) Penrose OR (and Orch OR) invoke non-computable influences from information embedded in spacetime geometry, potentially avoiding algorithmic determinism. In summary, Orch OR can account for real-time conscious causal agency, avoiding the need for consciousness to be seen as epiphenomenal illusion. Orch OR can rescue conscious free will.